Snails are just my speed! - McCloskey, Kevin (New York : Toon Books, 2018)
Looks at snails with a mix of science, art, and hilarity.
Kirkus Review, March 2018
2.9
K-3
490L
M
Keywords: Snails -- Juvenile literature; Snails; Readers (Elementary) -- Nonfiction; Nonfiction picture books